POST-COVID SYNDROME AND ITS LONG-TERM EFFECTS ON THE BODY: CLINICAL MANIFESTATIONS, TREATMENT AND REHABILITATION METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Post-COVID syndrome, also known as long COVID, refers to the persistence of symptoms and complications beyond the acute phase of COVID-19 infection. This article explores the clinical manifestations of the syndrome, its long-term effects on multiple organ systems, and evidence-based approaches to treatment and rehabilitation. Emphasis is placed on interdisciplinary care, patient-tailored rehabilitation programs, and the role of psychological support. The article synthesizes current scientific literature and clinical practices to provide a comprehensive framework for managing this emerging public health concern.